Erwerbstätigkeit auf Rekordniveau: Ergebnis richtiger Arbeitsmarktpolitik? - Sabine Klinger; Holger Bonin; Gustav A. Horn; Alexander Herzog-Stein; Daniel Ehing; Bernd Raffelhüschen (Wirtschaftsdienst, 2013)
Die Erwerbstätigkeit befindet sich in Deutschland auf einem Höchststand. Die Ursachen hierfür sind vielfältig und nicht nur in der vor zehn Jahren verabschiedeten Agenda 2010 zu sehen. Das gestiegene Bildungsniveau, die hohe Erwerbsbeteiligung, demografische Aspekte, die schrittweise Verschiebung des Rentenalters und nicht zuletzt die gute Konjunktur haben ebenfalls zum guten Ergebnis beigetragen. – – Employment in Germany reached another all-time high in 2012, growing faster than the economy. Most labour market segments participated. Some economists see labour market legislation and the changed behaviour of economic agents as the driving force though they also resulted in low to negative productivity growth, especially in the industrial sectors. The structural labour market reforms put the economy on a path towards a new equilibrium characterised by less structural unemployment. In addition, regained competitiveness due to wage restraint and increased labour supply have boosted employment. Other economists counter that the recent labour market reforms did not have any significant impact on the impressive employment performance in Germany. Instead, the crucial factors were employment gains in two successive economic booms and the successful safeguarding of jobs during the Great Recession. Another view is that the current labour force record was mainly caused by increased labour force participation of women and the elderly, which was driven by the reform of the public pension system.
Keywords: J1; J08; J26; 330; Erwerbstätigkeit; Arbeitsmarktpolitik; Hartz-Reform; Arbeitsmarktflexibilität; Beschäftigungseffekt; Deutschland